Study of wear resistance and nanostructure of tertiary Al2O3/Y2O3/CNT pulsed electrodeposited Ni-based nanocomposite - Mirzamohammadi, S.; Aliov, M.Kh.; Sabur, A.R.; Hassanzadeh-Tabrizi, A. (Фізико-хімічна механіка матеріалів, 2010)
Electrodeposition of tertiary Alumina/Yitria/carbon nanotube (Al2O3/Y2O3/CNT) nanocomposite by using pulsed current has been studied. Coating process has been performed in nickel sulphate bath and nanostructure of the obtained compound layer was examined with high precision figure analysis of SEM nanographs. The effects of process variables, i.e. Y2O3 concentration, treatment time, current density and temperature of electrolyte have been experimentally studied. Statistical methods were used to achieve the minimum wear rate and average size of nanoparticles. Finally the contribution percentage of different effective factors was revealed and confirmation run showed the validity of the obtained results. Also it has been revealed that by changing the size of nanoparticles, wear properties of coatings will change significantly. Atomic force microscopy (AFM) and transmission electron microscope (TEM) analysis have confirmed smooth surface and average size of nanoparticles in the optimal coating.